Analysis of genetic variation of the voltage-gated sodium chanel gene sequence in Aedes aegypti NCBI popset (2325355280) using in silico RFLP - Hafizhah Putrizalda; Afifatul Achyar (Tropical Genetics, 2024)
Aedes aegypti is a mosquito that belongs to the Culicinae Culicids family, order Diptera, class Insecta. This mosquito has the potential to transmit dengue hemorrhagic fever (DHF). DHF is a disease characterized by sudden fever, bleeding both in the skin and in the body and can cause shock and death. In-silico is a research approach whose use will be discussed with advances in technology and available databases. This approach is very commonly used in medical and other healthcare settings. The method used is to use the NCBI site, screen restriction enzymes with an insilico web and continue with the benchling site. The results obtained were using the NheI enzyme and producing two alleles namely Allele A1 and Allele A2. The A2 allele dominates because it has a fragment percentage of 63,3%.